Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1002/uog.6422
|View full text |Cite
|
Sign up to set email alerts
|

Twin growth discrepancy in early pregnancy

Abstract: Objectives To assess whether early fetal growth restriction in a twin, expressed as the intertwin discrepancy in crown-rump length (CRL) between two viable twins at 16.9% discrepancy (sensitivity, 88.9%; 95% CI, and specificity, 86.7%; 95% CI,. ConclusionThere is a significant relationship between CRL discrepancy at 7 + 0 to 9 + 6 weeks and the likelihood of subsequent single intrauterine fetal loss. This suggests that spontaneous fetal demise of one twin may be preceded by growth restriction in the first trim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 18 publications
1
39
0
Order By: Relevance
“…Current investigations found a significant correlation of fetal demise and discrepancy in CRL at the 11th-14th week scan in monochorionic twins (13). A difference in twins' CRL lengths <20% was usually found in twins that survived until due term, whereas when the CRL difference was >40%, a single loss was more common (14). In monochorionic twin pregnancies with a CRL discordance ≥ 10% the odds of birth weight discordance are three times higher than in concordant twins (8).…”
Section: Discussionmentioning
confidence: 89%
“…Current investigations found a significant correlation of fetal demise and discrepancy in CRL at the 11th-14th week scan in monochorionic twins (13). A difference in twins' CRL lengths <20% was usually found in twins that survived until due term, whereas when the CRL difference was >40%, a single loss was more common (14). In monochorionic twin pregnancies with a CRL discordance ≥ 10% the odds of birth weight discordance are three times higher than in concordant twins (8).…”
Section: Discussionmentioning
confidence: 89%
“…There are controversial data whether twins have a higher FPR due to the increased incidence of enlarged NT measurements observed in monochorionic pregnancies, almost 1.5 times larger compared with dichorionic twins, as suggested by Sebire et al 37 and Cheng et al 38 It is thought that this increased fetal NT is an early manifestation of TTTS 28,29 ; however, this finding is not consistent in other studies, which have noted nonsignificant differences in mean NT measurements between dichorionic twins, monochorionic twins, and singletons. 35,39 FIRST-TRIMESTER SCREENING First-trimester aneuploidy screening combining NT with serum markers (free B-hCG and PAPP-A) is well established in singleton pregnancies, with a detection rate of 82% for Down syndrome with a 5% FPR.…”
Section: Ntmentioning
confidence: 98%
“…28 In fact, a discrepancy <20% had a likelihood of a subsequent viable twin pregnancy of 97%, whereas no viable twins were found at the 11-to 14-week scan when the discrepancy was >60%. This suggests that discrepancies in very early fetal stages may more accurately Prenatal Diagnosis in Multiples 565…”
Section: Identification Of Twin Gestations At Increased Risk For Compmentioning
confidence: 99%
“…Several retrospective studies demonstrated that an intertwin CRL disparity identified early in the first trimester might predict several adverse perinatal outcomes or even fetal loss [31][32][33]. However, some of the studies excluded monochorionic gestations, whereas the majority of them included a relatively limited number of patients.…”
Section: Crown-rump Length Discordance and Perinatal Outcomementioning
confidence: 99%
“…135 Retrospective MC Not included 5-20% Shahshahan [43] 118 Prospective DC Not included 11% Fareeduddin [42] 78 Retrospective DC Not included 9% Bhide [39] 507 Retrospective MC and DC Included 12.2-19.3% Bora [32] 77 Retrospective MC and DC Included 16.9% Banks [41] 108 Retrospective DC Not included 5% Tai [40] 178 Retrospective MC and DC Not included 11.1% Salomon [37] 182 Prospective MC and DC Included 14.3%…”
mentioning
confidence: 99%